A tissue-specific role of membrane-initiated ERα signaling for the effects of SERMs. Issue 2 (29th March 2022) - Gustafsson, Karin L; Movérare-Skrtic, Sofia; Farman, Helen H; Engdahl, Cecilia; Henning, Petra; Nilsson, Karin H; Scheffler, Julia M; Sehic, Edina; Islander, Ulrika; Levin, Ellis; Ohlsson, Claes; Lagerquist, Marie K
Abstract : Selective estrogen receptor modulators (SERMs) act as estrogen receptor (ER) agonists or antagonists in a tissue-specific manner. ERs exert effects via nuclear actions but can also utilize membrane-initiated signaling pathways. To determine if membrane-initiated ERα (mERα) signaling affects SERM action in a tissue-specific manner, C451A mice, lacking mERα signaling due to a mutation at palmitoylation site C451, were treated with Lasofoxifene (Las), Bazedoxifene (Bza), or estradiol (E2), and various tissues were evaluated. Las and Bza treatment increased uterine weight to a similar extent in C451A and control mice, demonstrating mERα-independent uterine SERM effects, while the E2 effect on the uterus was predominantly mERα-dependent. Las and Bza treatment increased both trabecular and cortical bone mass in controls to a similar degree as E2, while both SERM and E2 treatment effects were absent in C451A mice. This demonstrates that SERM effects, similar to E2 effects, in the skeleton are mERα-dependent. Both Las and E2 treatment decreased thymus weight in controls, while neither treatment affected the thymus in C451A mice, demonstrating mERα-dependent SERM and E2 effects in this tissue. Interestingly, both SERM and E2 treatments decreased the total body fat percent in C451A mice, demonstrating the ability of these treatments to affect fat tissue in the absence of functional mERα signaling. In conclusion, mERα signaling can modulate SERM responses in a tissue-specific manner. This novel knowledge increases the understanding of the mechanisms behind SERM effects and may thereby facilitate the development of new improved SERMs.